Out-of-Hospital Cardiac Arrest Due to Ventricular Fibrillation in a 5-Year-Old Pediatric Patient - Klučka, Jozef; Juřenčák, Tomáš; Štourač, Petr; Vít, Pavel; Foralová, Vladimíra; Synková, Iva (Pediatric emergency care, 2020)
Out-of-hospital cardiac arrest in pediatric population is rare and predominantly has respiratory aetiology. Authors present the relatively unique case of out-of hospital cardiac arrest in 5-years old pediatric patient due to ventricular fibrillation (VF) as the initial rhythm during the advanced life support. The patient was resuscitated by his parents and the initial rhythm was VF. After defibrillation the patient was admitted to the pediatric intensive care were another two episodes of VF was detected and treated. After standard postresuscitation care, patient was weaned from sedation and extubated with good neurologic outcome. Genetic screening of the 7 genes associated with cardiac channelopathies (KCNQ1, KCNH2, SCN5A, KCNE1, KCNE2, RYR2, CASQ2) found mutation in gene KCHN2 and gene SCN5A, that were according to actual data considered benign. This case highlights the need for automated external defibrillator implementation in basic life support also in pediatric population and possible role of genetic predisposition in emergence of fibrillation.
Keywords: Genetic Predisposition to Disease; NAV1.5 Voltage-Gated Sodium Channel; Cardiopulmonary Resuscitation; mužské pohlaví; mutace; Ventricular Fibrillation; kardiopulmonální resuscitace; draslíkový kanál ERG1; Child, Preschool; fibrilace komor; Mutation; Humans; předškolní dítě; Out-of-Hospital Cardiac Arrest; ERG1 Potassium Channel; genetická predispozice k nemoci; zástava srdce mimo nemocnici; napěťově řízený sodíkový kanál, typ 5; lidé; Male